Online interactive activities to learn Ramayana epic by primary Tamil students - Letchumanan, Kanthimathi; Muthusamy, Paramasivam; Govindasamy, Potchelvi; Farashaiyan, Atieh (Canadian Center of Science and Education, 2016)
The Ramayana epic has many moral values that can be used as guidance in our daily life especially for the development of a person towards a better direction. Besides this, there are many other lessons that can be learned from within each Ramayana epic stories, for example, the values and norms, customs, mannerism lessons and the various characteristics of people and so on. But today’s digital or Net Generation teenagers do not find reading Ramayana as fun or interesting because of its text form. The technology is more advanced and Ramayana epics look very ancient in the eyes of this Digital Natives. This study used the idea of gamification, a game play mechanics to create meaningful learning experiences and make the learning more interesting and fun. Gamification also looks at games and learning from a different angle on how to make learning more meaningful, engaging, interactive, fun and interesting. In view of this, this research aims to seek if the use of online interactive activities could encourage and motivate teenagers to read Ramayana epics. Forty Primary Tamil students participated in this study voluntarily. The data were collected through a questionnaire. Based on the pre-questionnaire data regarding respondents’ prior knowledge on Ramayana, it was found that respondents had minimal knowledge about it. 37% said they would like to read the epic through comic books and 63% claimed that they would prefer computer. This study has some implications for computer assisted language learning.